The Problem of Adaptation of the Generalized Neural Element - E. V. Konovalov (Моделирование и анализ информационных систем)
A perspective model of the neuron cell | the generalized neural element (GNE) is studied in this article. This model has the universal character. It combines properties of the neuron-oscillator and the neuron-detector. The problem of adaptation of the generalized neural element is formulated and solved.